Design, synthesis, docking, ADMET studies, and anticancer evaluation of new 3-methylquinoxaline derivatives as VEGFR-2 inhibitors and apoptosis inducers - Mohammed M. Alanazi; Ibrahim H. Eissa; Nawaf A. Alsaif; Ahmad J. Obaidullah; Wael A. Alanazi; Abdullah F. Alasmari; Hussam Albassam; Hazem Elkady; Alaa Elwan (Taylor & Francis Group, 2021)
Vascular endothelial growth factor receptor-2 (VEGFR-2) plays a critical role in cancer angiogenesis. Inhibition of VEGFR-2 activity proved effective suppression of tumour propagation. Accordingly, two series of new 3-methylquinoxaline derivatives have been designed and synthesised as VEGFR-2 inhibitors. The synthesised derivatives were evaluated in vitro for their cytotoxic activities against MCF-7and HepG2 cell lines. In addition, the VEGFR-2 inhibitory activities of the target compounds were estimated to indicate the potential mechanism of their cytotoxicity. To a great extent, the results of VEGFR-2 inhibition were highly correlated with that of cytotoxicity. Compound 27a was the most potent VEGFR-2 inhibitor with IC50 of 3.2 nM very close to positive control sorafenib (IC50 = 3.12 nM). Such compound exhibited a strong cytotoxic effect against MCF-7 and HepG2, respectively with IC50 of 7.7 and 4.5 µM in comparison to sorafenib (IC50 = 3.51 and 2.17 µM). In addition, compounds 28, 30f, 30i, and 31b exhibited excellent VEGFR-2 inhibition activities (IC50 range from 4.2 to 6.1 nM) with promising cytotoxic activity. Cell cycle progression and apoptosis induction were investigated for the most active member 27a. Also, the effect of 27a on the level of caspase-3, caspase-9, and BAX/Bcl-2 ratio was determined. Molecular docking studies were implemented to interpret the binding mode of the target compounds with the VEGFR-2 pocket. Furthermore, toxicity and ADMET calculations were performed for the synthesised compounds to study their pharmacokinetic profiles